Spiral of Silence Through the Hashtag #Tolakpolitikbusuk: Opinion Research on Limiting the Political Rights of Ex-Corruptors as Legislative Candidates. - Oktafia, Bella; Rukmini, Diah; Zahro, Siti Khoirun Nabilatuz (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
General Elections are important moments in the democratic life of a country, where the people have the opportunity to choose their leaders and representatives. The General Election Commission as a General Election institution stipulates General Election Commission Regulations Number 14 of 2018 and Number 20 of 2018 which regulate the prohibition of former corruption convicts from becoming legislative candidates. Because many parties oppose and support this, the 2019 election law stipulates that ex-corruptors can nominate themselves as members of the legislature on condition that they must be fair and honest, admitting to the public that the person concerned is an ex-corruptor. This research method uses descriptive qualitative, using the spiral of silence theory, namely a media theory that pays more attention to majority views and suppresses minority views. The results of the research are: The results of this research, people tend to assess the pros and cons before people write opinions via their Twitter accounts with the hashtag #tolakpolitikbusuk as an expression of how they want leaders who are ’clean’, clean in the sense here are those who have never been involved in cases that harm many people. Indonesia is a democratic country, but voicing the voice of the people is quite difficult. The reality is that it confronts the expectations that occur in society.